Infective endocarditis in the Lao PDR: clinical characteristics and outcomes in a developing country. - Mirabel, M; Rattanavong, S; Frichitthavong, K; Chu, V; Kesone, P; Thongsith, P; Jouven, X; Fournier, P; Dance, D; Newton, P (Elsevier, 2015)
INTRODUCTION: Data on infective endocarditis (IE) in Southeast Asia are scarce. OBJECTIVES: To describe the clinical epidemiology of IE in Lao PDR, a lower middle-income country. METHODS: A single centre retrospective study at Mahosot Hospital, Vientiane. Patients aged over 1year of age admitted 2006-2012 to Mahosot Hospital with definite or possible IE by modified Duke criteria were included. RESULTS: Thirty-six patients fulfilled the inclusion criteria; 33 (91.7%) had left-sided IE. Eleven (30.6%) had definite IE and 25 (69.4%) possible left-sided IE. Median age was 25years old [IQR 18-42]. Fifteen patients (41.7%) were males. Underlying heart diseases included: rheumatic valve disease in 12 (33.3%), congenital heart disease in 7 (19.4%), degenerative valve disease in 3 (8.3%), and of unknown origin in 14 (38.9%) patients. Native valve IE was present in 30 patients (83.3%), and prosthetic valve IE in 6 patients (16.7%). The most frequent pathogens were Streptococcus spp. in 7 (19.4%). Blood cultures were negative in 22 patients (61.1%). Complications included: heart failure in 11 (30.6%), severe valve regurgitation in 7 (19.4%); neurological event in 7 (19.4%); septic shock or severe sepsis in 5 (13.9%); and cardiogenic shock in 3 patients (8.3%). No patient underwent heart surgery. Fourteen (38.9%) had died by follow-up after a median of 2.1years [IQR 1-3.2]; and 3 (8.3%) were lost to follow-up. CONCLUSIONS: Infective endocarditis, a disease especially of young adults and mainly caused by Streptococcus spp., was associated with rheumatic heart disease and had high mortality in Laos.